Investigation of Retorted Water Produced by Direct and Indirect Methods of Oil Shale Pyrolysis: استقصاء المياه الناتجة من عملية التحليل الحراري للصخر الزيتي بواسطة الطرق المباشرة والغير مباشرة - Ola Majdi Abuhanieh, Omar Al-Ayed, Sura Harahsheh (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2021)
The oil shale retorting process produces petroleum like liquid that requires hydro treatment and refining process to produce normal distillation fractions. The retorting process produces shale oil in addition to hydrocarbon gases and retorted water. The tests have shown total water content (3.19%wt, at heating rate 5 OC/min using TGA at 400 OC. This characterization method utilized different analytical techniques. X-ray diffraction analytical techniques confirmed that the main minerals in the oil shale were calcite and quartz. On the other hand, phenol content was measured and found to be 23.7 ppm using HPLC device. Arsenic was traced in the retorted water and found to be 1.437 ppm which is lower than the Uranium which formed in 0.004 ppm. Sulphate found to be 0.45 ppm using spectrophotometer device. And the Aluminum is found 3.09 ppm of in the present work, Vanadium was formed 0.0244 ppm, Thorium is less than 0.03 ppm, and Zn present in the retorted water was found to be 1.82 ppm using ICP device. Two methods used to produce retorted water, direct method using oxygen gas, and in-direct method (absence oxygen with N2 gas). The results of the two methods are comparable.